Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1088/1742-6596/1317/1/012143
|View full text |Cite
|
Sign up to set email alerts
|

Promoting indonesian secondary school students’ argumentation skills in the concept of chemistry reaction-rate: a comparative effect of three cooperative learning strategies

Abstract: Argumentation skills have been minimally fostered in the worldwide science classrooms that brings students’ low ability to make scientific arguments. This study had compared the effect of the strategies of jigsaw, two-stay-two-stray (TSTS), and discovery-learning (DL) in promoting Indonesian secondary school student’s argumentation skills in the concept of chemistry reaction-rate. Data were collected using open-ended tests and video observations. The results of quantitative analysis show that jigsaw and TSTS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In our previous study, we had used jigsaw, TSTS, and DL strategies to promote secondary school students' ability in making argumentation in chemistry. We found that these strategies were effective in engaging the students making argumentations about the concept-to-learn [19]. In addition, IbL had also been effective in improving students' knowledge in science, and their reasoning and argumentation skills about the learnedconcept [10].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In our previous study, we had used jigsaw, TSTS, and DL strategies to promote secondary school students' ability in making argumentation in chemistry. We found that these strategies were effective in engaging the students making argumentations about the concept-to-learn [19]. In addition, IbL had also been effective in improving students' knowledge in science, and their reasoning and argumentation skills about the learnedconcept [10].…”
Section: Introductionmentioning
confidence: 79%
“…In shorts, the steps of those strategies did not explicitly direct the students about when and how to make the argumentations. As a result, some students were observed confused to construct the argumentations [19]. This finding indicates that a learning strategy which is not tailored with specific steps of making arguments -such as those threewill engage students minimally in making scientific argumentation.…”
Section: Introductionmentioning
confidence: 99%
“…While the 4SJ model is effective for improving students' argumentation skills on salt hydrolysis material. This can happen because in the learning process these two models have the opportunity to manage information and improve communication skills so that all students will be involved and will have a positive impact on student learning outcomes (Effendi- Hasibuan et al 2019). However in the 4SJ class, the learning process is more effective than the jigsaw class because the syntax is shorter so that students have more time to discuss.…”
Section: Fig 2 Level Of Argumentation Ability Of Students' Posttest Scoresmentioning
confidence: 99%
“…So that the discussion time with the group is more intensive. According to Effendi- Hasibuan et al (2019) in the jigsaw learning process students have the opportunity to manage information and improve communication skills so…”
Section: Fig 2 Level Of Argumentation Ability Of Students' Posttest Scoresmentioning
confidence: 99%
“…The ADI learning model is usually used in the classroom or with a face-to-face system. Effendi-Hasibuan et al (2019a) report obstacles to the ADI model, especially the lack of time at the argument production stage, so an innovation is needed to solve this problem (Effendi-Hasibuan et al 2019b). Innovation, such as designing the model with blended learning, is in accordance with Divena et al (2021) research, who carried out the ADI model independently online.…”
Section: Introductionmentioning
confidence: 99%